Badanie "International Civic and Citizenship Education Study" (ICCS) - źrodło nowych danych o młodzieży = Project "International Civic and Citizenship Education Study" (ICCS) - a New Source of Data about Young People - Koseła, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present the results of a project "International Civic and Citizenship Education Study" executed in the winter and early spring of 2009. It also introduces the research issues and encourages to use the data when it is available for analysis. The subject of the research were 14-year-old students, teachers running their classes and headmasters of the schools which were drawn to investigate the students and teachers.
Keywords: "International Civic and Citizenship Education Study" (ICCS); młodzież; badania